PENGARUH PENGALAMAN BELAJAR EKONOMI DAN LITERASI DIGITAL TERHADAP KETERAMPILAN MENGAJAR ABAD 21 - Rani Nur Mayasari; Suparno, Suparno; Pratama, Aditya (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to explore the impact of economics and digital literacy learning experiences on the development of 21st century teaching skills. Primary data was obtained from 161 samples of students majoring in education at the Faculty of Economics, Jakarta State University who had taken part in teaching skills practice (PKM). The SEM-PLS analysis method is used to analyze the relationship between variables. The research results confirm the significant role of digital literacy education in influencing the development of 21st century teaching skills, both directly and indirectly through economic learning experiences. However, this research is limited to one university and limited variables, namely economic learning experience, digital literacy, and 21st century teaching skills. Despite these limitations, this research provides valuable insights for the development of 21st century teaching skills. Improving the economic learning experience and digital literacy for education students undergoing Teaching Skills Practice (PKM) at Jakarta State University is considered a strategic step to prepare prospective educators to face the demands of the modern era. The implications of this research can be a basis for universities and other educational institutions to design learning programs that are more effective and relevant in developing 21st century teaching skills. Thus, this research provides an important contribution to understanding and thinking regarding the formation of adaptive and competent teaching staff in facing the dynamics of today's education.